Serial long-term evaluation of neointimal stent coverage and thrombus after sirolimus-eluting stent implantation by use of coronary angioscopy. Issue 12 (14th November 2007) - Takano, Masamichi; Yamamoto, Masanori; Xie, Yong; Murakami, Daisuke; Inami, Shigenobu; Okamatsu, Kentaro; Seimiya, Koji; Ohba, Takayoshi; Seino, Yoshihiko; Mizuno, Kyoichi
Abstract : Objective: Progression of neointimal stent coverage (NSC) and changes in thrombus were evaluated serially by coronary angioscopy for up to 2 years after sirolimus-eluting stent (SES) implantation. Design: Serial angioscopic observations were performed in 20 segments of 20 patients at baseline, and at 6 months and 2 years after SES implantation. NSC was classified as follows: 0, uncovered struts; 1, visible struts through thin neointima; or 2, no visible struts. In each patient, maximum and minimum NSC was evaluated. Existence of thrombus was also examined. Results: The maximum NSC increased from 6 months to 2 years (1.2 (0.4) vs 1.8 (0.4), respectively, p = 0.005), while the minimum NSC did not change (0.7 (0.5) vs 0.8 (0.4), respectively, p = 0.25). The prevalence of patients with uncovered struts did not decrease from 6 months to 2 years (35% vs 20%, respectively, p = 0.29). Although there were no thrombus-related adverse events, new thrombus formation was found in one patient (5%) at the 6-month, and in four patients (20%) at the 2-year follow-up evaluations. Frequencies of thrombus inside the SES at baseline, 6 months and 2 years did not differ one from another (40%, 40% and 30%, respectively; p = NS). Conclusions: Neointimal growth inside the SES progressed heterogeneously. Uncovered struts persisted in 20% of the patients for up to 2 years and subclinical thrombus formation was not a rare phenomenon.